A systematic review of factors associated with student use of campus food pantries: implications for addressing barriers and facilitating use - Oisemujaime Victoria Idehai; Pindar Mbaya; Tammy Chung; Trishnee Bhurosy (BMC, 2024)
Abstract Background While campus food pantries have been important safety net programs for alleviating food insecurity among college students, factors related to accessing these vital resources have not been fully researched and summarized. This study systematically synthesized peer-reviewed literature on the predictors, barriers to, and facilitators of using campus food pantries among college students. Methods A search was conducted on PubMed, CINAHL Complete, PsychInfo, PsycARTICLES, and ScienceDirect in April 2023. Included studies needed to be peer-reviewed, written in English, and focused on college or university students. Three authors independently screened all articles retrieved from the five databases based on titles, titles and abstracts, and a full article review. The Study Quality Assessment Tool from the National Heart, Lung, and Blood Institute was used to assess the risk of bias in the included cross-sectional studies. The risk of bias and quality of mixed methods or qualitative studies were assessed as well. Results Eight studies were included in the systematic review. Students likely to use a college food pantry were food-insecure, who most often identified as Asian, Hispanic/Latino, Filipino or Pacific Islander; were first-generation to college; international students; sophomores and juniors; had student loans; were living off-campus; and were without stable housing. Stigma was the most frequently mentioned barrier to using a food pantry. Participants mentioned facilitators such as convenient location and hours of operation, access to fresh produce and nutritious and safe foods, availability of a variety of foods, friendly and helpful service, social support, and awareness of a pantry through fellow students and other members of the university such as staff and faculty. Conclusions Continued research must address students' systemic barriers to accessing food pantries. Campus food pantry leaders, university administrators, and policymakers need to work together to create cost-effective and sustainable solutions that will alleviate the stigma and burden of food-insecure students and provide them with safe, nutritious, and culturally acceptable foods.